Review: Neurological Complications From Therapies for Pediatric Brain Tumors - Nguyen, Thien; Mueller, Sabine; Malbari, Fatema (Frontiers in Oncology, 2022)
Surgery, chemotherapy and radiation have been the mainstay of pediatric brain tumor treatment over the past decades. Recently, new treatment modalities have emerged for the management of pediatric brain tumors. These therapies range from novel radiotherapy techniques and targeted immunotherapies to checkpoint inhibitors and T cell transfer therapies. These treatments are currently investigated with the goal of improving survival and decreasing morbidity. However, compared to traditional therapies, these novel modalities are not as well elucidated and similarly has the potential to cause significant short and long-term sequelae, impacting quality of life. Treatment complications are commonly mediated through direct drug toxicity or vascular, infectious, or autoimmune mechanisms, ranging from immune effector cell associated neurotoxicity syndrome with CART-cells to neuropathy with checkpoint inhibitors. Addressing treatment-induced complications is the focus of new trials, specifically improving neurocognitive outcomes. The aim of this review is to explore the pathophysiology underlying treatment related neurologic side effects, highlight associated complications, and describe the future direction of brain tumor protocols. Increasing awareness of these neurologic complications from novel therapies underscores the need for quality-of-life metrics and considerations in clinical trials to decrease associated treatment-induced morbidity.